A cell penetrating peptide from SOCS-1 prevents ocular damage in experimental autoimmune uveitis. (December 2018) - Ahmed, Chulbul M.; Massengill, Michael T.; Brown, Emily E.; Ildefonso, Cristhian J.; Johnson, Howard M.; Lewin, Alfred S.
Abstract: We describe an immunosuppressive peptide corresponding to the kinase inhibitory region (KIR) of the intracellular checkpoint protein suppressor of cytokine signaling 1 (SOCS-1) that binds to the phospho-tyrosine containing regions of the tyrosine kinases JAK2 and TYK2 and the adaptor protein MAL, and thereby inhibits signaling downstream from these signaling mediators. The peptide, SOCS1-KIR, is thus capable of downregulating overactive JAK/STAT or NF-kB signaling in somatic cells, including those in many compartments of the eye. Attachment of poly-arginine to this peptide (R9-SOCS1-KIR) allows it to penetrate the plasma membrane in aqueous media. R9-SOCS1-KIR was tested in ARPE-19 cells and was found to attenuate mediators of inflammation by blocking the inflammatory effects of IFNγ, TNFα, or IL-17A. R9-SOCS1-KIR and also protected against TNFα or IL-17A mediated damage to the barrier properties of ARPE-19 cells, as evidenced by immunostaining with the tight junction protein, zona occludin 1 (ZO-1), and measurement of transepithelial electrical resistance (TEER). Experimental autoimmune uveitis (EAU) was generated in B10. RIII mice using a peptide of interphotoreceptor retinal binding protein (IRBP 161−180 ) as immunogen. Topical administration of R9-SOCS1-KIR, 2 days before (prophylactic), or 7 days after immunization (therapeutic) protected ocular structure and function as seen by fundoscopy, optical coherence tomography (OCT), and electroretinography (ERG). The ability R9-SOCS1-KIR to suppress ocular inflammation and preserve barrier properties of retinal pigment epithelium makes it a potential candidate for treatment of autoimmune uveitis. Highlights: The kinase inhibitory region of SOCS-1 linked to poly-arginine (R9-SOCS1-KIR) and its inactive control peptide were synthesized. R9-SOCS1-KIR attenuated pro-inflammatory effects of IFNγ, TNFα, and IL-17 in ARPE-19 cells, thus showing a simultaneous inhibition Th1 and Th17 cell functions. Damage to barrier properties of ARPE-19 cells caused by TNFα or IL-17 was prevented in the presence of R9-SOCS1-KIR. Topical delivery of R9-SOCS1-KIR, 2 days before or 7 days after immunization prevented damage in a mouse model of experimental autoimmune uveitis.